Pengaruh Debt To Assets Ratio (DAR) dan Debt To Equity Ratio (DER) terhadap Return On Equity (ROE) : (Pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Tahun 2018-2021) - Wahyu Toni Hidayat; Erwin Saputra Siregar; Puteri Anggi Lubis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Financial Services Authority (OJK) stated that the improving conditions of the Covid-19 Pandemic had an impact on Indonesia's economic growth with growth in Q4-2021 of 5.02% (yoy). In maintaining the momentum of economic recovery during the Covid-19 pandemic, the sharia financial services industry also experienced positive growth with Indonesian sharia financial assets able to grow by 13.82% (yoy) to IDR 2,050.44 trillion in 2021, and the previous year 2020 amounted to IDR 1,801.40 trillion, while in 2019 it amounted to IDR 1,291.48 trillion and in 2018 it amounted to IDR 1,265.97 trillion. This shows that sharia finance is able to survive well during the Covid-19 era. This research aims to determine the effect of Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER) on Return On Equity (ROE) in companies listed on the Jakarta Islamic Index (JII) for the 2018-2021 period. The method used in this research is quantitative research methods. The sample used is companies registered on the Jakarta Islamic Index (JII). Based on the purpose sampling method, there were 9 companies that met the criteria. The results of this research show that partially the Debt to Assets Ratio (DAR) has no significant effect on Return On Equity (ROE), while the Debt to Equity Ratio (DER) has a significant effect on Return On Equity (ROE) in Jakarta Islamic Index companies. This research also shows that simultaneously Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER) have a significant effect on Return On Equity (ROE) in Jakarta Islamic Index companies.